Five years of research on improved fallow in the semiarid highlands of Rwanda - Balasubramanian, V.; Sekayange, L. (1992)
Alternative technologies that maximize the use oflocal resources and improve the sustainability of crop production in Rwanda are needed. Promising species for the semi-arid highlands, where the research reported in this paper was conducted, include mucuna (Mucunaprwiens) for fallow periods of 1 4- 1 8 weeks, sunnhemp (Crotalaria ochroleuca), pigeonpea (Cajanus cajan) and desmodium (Desmodium distortum) for fallow periods of 20-24 weeks, and Sesbania sesban and Tephrosia vogelii for long fallows ofa year or more. In crop rotations, these legumes contribute 17-240 kg N/ha to associated non-legume crops. However, two seasons of growth are needed for there to be a marked effect on crop yields and the beneficial effect of the legumes lasts only for one or two seasons after the incorporation of biomass. The legumes also supply nutrients recycled from the soil.